Chemical, Microstructural, and Rheological Characterizations of Binders to Evaluate Aging and Rejuvenation. Issue 1 (2017) - Osmari, Patrícia Hennig; Aragão, Francisco Thiago Sacramento; Leite, Leni Figueiredo Mathias; Simão, Renata Antoun; da Motta, Laura Maria Goretti; Kim, Yong-Rak
This study evaluated the effects of the commercial product, AR 5, and two alternative products, waste cooking oil and castor oil, in the rejuvenation process of two asphalt binders. The analyses were carried out on microscopic and macroscopic scales on virgin, aged, and rejuvenated binders. Tests in a dynamic shear rheometer were performed to characterize rheological properties of the binders. Then, an atomic force microscope was used to identify microstructural changes in the materials. A digital image analysis technique enabled the quantification of key variables such as area fraction and spatial and size distributions of the binder constituents. Finally, the following chemical tests were performed to identify changes in the chemical composition of the binders resulting from the aging and rejuvenation processes: SARA (which measures saturates, asphaltenes, resins, and aromatics), gel permeation chromatography, and nuclear magnetic resonance. The results obtained from the tests were further compared to identify correlations between the properties evaluated in different scales. The results demonstrated the efficiency and potential of the rejuvenators evaluated in this study. The results also highlighted the importance of the use of advanced techniques to characterize and understand the material aging and rejuvenation processes.